Ammonia as an efficient COx-free hydrogen carrier: Fundamentals and feasibility analyses for fuel cell applications - Cha, Junyoung; Jo, Young Suk; Jeong, Hyangsoo; Han, Jonghee; Nam, Suk Woo; Song, Kwang Ho; Yoon, Chang Won (ELSEVIER SCI LTD, 2018)
A COx-free 1 kW-class hydrogen power pack fueled by liquid ammonia is presented. For applications in a practical-scale hydrogen production system in conjunction with a polymer electrolyte membrane fuel cell, Ru catalysts supported on La-doped alumina (Ru/La(x)-Al2O3) were pelletized by varying the lanthanum doping content (x mol%) to control catalytic activities. An optimized Ru(1.06 wt%)/La(20)-Al2O3 pellet catalyst presents a > 99.7% conversion efficiency at 500 degrees C under a gas hourly space velocity of 5000 mL g(cat)(-1)h(-1). Various materials were screened to remove residual ammonia from the product stream, and the X zeolite was chosen as a highly capable adsorbent. Based on the synthesized catalyst and screened adsorbent, a power pack consisting of a dehydrogenation reactor, an adsorbent tower, and a 1 kW-class polymer electrolyte membrane fuel cell was designed and manufactured. The as -integrated system can convert 9 L min(-1) of ammonia into 13.4 L min(-1) of hydrogen, powering a 1 kW-class fuel-cell continuously for > 2 h without any performance degradation. To achieve autothermal and COx-free operations, heat required for ammonia dehydrogenation was provided by unutilized hydrogen from the fuel cell, drastically increasing the overall efficiency of the system to > 49% while removing the external heat source, isobutane. Finally, a drone tethered to the system was operated, demonstrating the feasibility of an elongated flight time of > 4 h, much longer than 14 min with Li-polymer battery loaded on the drone. The system is expected to meet the United States Department of Energy's 2020 gravimetric and volumetric hydrogen storage targets of 4.5 wt% and 30 gH(2) L-1 at system weights of 43 kg and 50 kg, respectively.
Keywords: SODIUM-BOROHYDRIDE; STORAGE MATERIAL; DECOMPOSITION; GENERATION; CATALYSTS; OXIDE; SELECTIVITY; ADSORPTION; CHALLENGES; PROGRESS